Alternative protein innovations and challenges for industry and consumer: an initial overview - Hefferon, Kathleen L.; De Steur, Hans; Perez-Cueto, Federico J. A.; Herring, Ronald (Frontiers in Sustainable Food Systems, 2023)
Over one fourth of today's greenhouse gas emissions are the result of agriculture, with the production of meat representing a large portion of this carbon footprint. As the wealth of lowand middle-income countries continues to increase, the demand for animal-sourced protein, such as dairy and meat products, will escalate. At this point in time, livestock feed alone utilizes almost 40% of the world's cropland. The rapidly increasing world population, coupled with a need for environmental sustainability, has renewed our attention on animal-protein substitutes.Apprehensions over climate change have aided an acceleration in the research and development of alternative proteins, which may replace some animal-sourced protein over time. The alternative dairy and meat industry is developing at a yearly rate of 15.8% and is predicted to reach 1.2 trillion USD by 2030. This emerging market incorporates new technologies in plantmade protein production, manufacturing of animal proteins by fermentation using microbial bioreactors, and accelerated production of cultivated (also known as cell-based) meat. These new technologies should change the global market drammatically. This article describes the history of the alternative protein industry and its' current status, then offers predictions of future pathways for this rapidly accelerating market. More speculatively, it discusses factors that lead to shifts in consumer behavior that trend toward the adoptation of new technologies.